La pace e le guerre: il nuovo scenario della globalizzazione - Letizia Schietroma (Democrazia e Diritti Sociali, 2022)
The topic of peace and its analytical study must be understood in a global and international context such as the one we currently live in. Despite this, it is still difficult to take this word for granted: peace. In fact, the history of war is uninterrupted in the history of humanity. Today many wars are fought, in different ways. And in this context the theme of globalization is inserted since, often, a war has repercussions not only human but also economic-financial in other parts of the world. Globalization, which today is witnessing an important change, has redeclined in much more porous terms what was once a rigid internal/external boundary. We must intervene with projects that take into account a system of building peace itself, overcoming the sovereignty of the state, paradigms of global justice, within institutions capable of promoting this.